2007
DOI: 10.1159/000108914
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Activity and Decline as Prognostic Indicators of Cardiovascular and Cerebrovascular Events: The ‘PROOF’ Study

Abstract: Background: Transversal studies have underlined the association between the decline in autonomic nervous system (ANS) activity and all-cause mortality. However, the predictive value of ANS has never been prospectively assessed in a general population-based cohort. Method: The PROOF (PROgnostic indicator OF cardiovascular and cerebrovascular events) cohort study was designed to prospectively assess the predictive value of ANS activity level in the general population, with regard to cardiovascular and cerebrovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 116 publications
2
83
0
Order By: Relevance
“…The details of the PROOF study have been previously described. 13 Briefly, the subjects were recruited from SaintEtienne, France, from 2001 to 2003 and were eligible if they were 65 y old at the inclusion date. The exclusion criteria were defined as follows: previous myocardial infarction, arrhythmia, cardiac pacemaker, stroke, neurological or psychiatric disease, insulin-dependent diabetes, chronic obstructive pulmonary disease, cerebral magnetic resonance results suggesting neurological diseases or initial dementia, and current residence in institutions.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the PROOF study have been previously described. 13 Briefly, the subjects were recruited from SaintEtienne, France, from 2001 to 2003 and were eligible if they were 65 y old at the inclusion date. The exclusion criteria were defined as follows: previous myocardial infarction, arrhythmia, cardiac pacemaker, stroke, neurological or psychiatric disease, insulin-dependent diabetes, chronic obstructive pulmonary disease, cerebral magnetic resonance results suggesting neurological diseases or initial dementia, and current residence in institutions.…”
Section: Populationmentioning
confidence: 99%
“…The Prognostic Indicator of Cardiovascular and Cerebrovascular Events (PROOF) study 13 provides an opportunity to examine the association between OS and self-reported sleep quality and duration in a larger sample of community-dwelling elderly with homogenous age, without insomnia complaints, and with no report of major health disease or previous diagnosis or treatment for OS. Sleep duration was assessed using a validated sleep questionnaire for self-reported sleep, i.e., the Pittsburgh Sleep Quality Index (PSQI), 14 that assesses more…”
Section: Introductionmentioning
confidence: 99%
“…The design of the PROOF study has been previously published. 10 In this study, we excluded subjects who were being treated for hypertension at inclusion (with angiotensin-converting enzyme inhibitors, angiotensinreceptor blockers, b-blockers, diuretics, calcium channel blockers or other antihypertensive drugs). This information was collected through subjects' selfreport and confirmed by physicians' prescriptions.…”
Section: Study Populationmentioning
confidence: 99%
“…The present investigation is part of the PROOF study, a population-based cohort study of 1,011 (61% females) volunteers aged 65¡1 yrs living in the town of Saint-Etienne (France) who were enrolled to assess whether an age-related decrease in autonomic nervous system activity could represent an independent risk for cardiovascular mortality, silent and symptomatic ischaemic stroke, myocardial infarction and newonset heart failure [30]. An ancillary study addressing the association between SDB and cardiovascular and cerebrovascular morbidity during a 7-yr follow-up was proposed to participants (SYNAPSE study).…”
Section: Populationmentioning
confidence: 99%